2022
DOI: 10.1055/a-1947-3174
|View full text |Cite
|
Sign up to set email alerts
|

Relative Energy Deficiency in Sport (RED-S) in Adolescents – A Practical Review

Abstract: There are many immediate and longer-term physical, psychological and metabolic benefits of being active during adolescence. These benefits exist when exercise and physical activity are undertaken in a state of energy balance. When exercise occurs in an environment of low energy availability, this is currently termed relative energy deficiency in sport and there are potential significant negative effects on mental well-being, bone, endocrine and metabolic health. Therefore, relative energy deficiency in sport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 111 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…Despite many studies investigating the prevalence of LEA, RED-S, and its symptoms (45), the literature on treatment options is surprisingly scarce. Consensus statements address the treatment options for athletes with LEA (65,78), and review papers provide an overview and recommendations of treatment strategies (12,28,39,71,82). However, there are only a handful of trials (13,29,34,40,77) and case studies (3,18,37,51) which have directly investigated improving EA in those with LEA (Table 1).…”
Section: Treatment Of Relative Energy Deficiency In Sportmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite many studies investigating the prevalence of LEA, RED-S, and its symptoms (45), the literature on treatment options is surprisingly scarce. Consensus statements address the treatment options for athletes with LEA (65,78), and review papers provide an overview and recommendations of treatment strategies (12,28,39,71,82). However, there are only a handful of trials (13,29,34,40,77) and case studies (3,18,37,51) which have directly investigated improving EA in those with LEA (Table 1).…”
Section: Treatment Of Relative Energy Deficiency In Sportmentioning
confidence: 99%
“…Reducing EEE is not always necessary, and an adequate EA can be achieved by an increase in EI alone (13,77). However, discussions with athletes, coaches, parents, and support teams may be useful to understand the athlete's overall physical demands for training, competing, other activities such as walking, other sports/teams, and work/educational commitments which may significantly contribute to their daily EEE and to canvas their views on a potential reduction (28,72). The inclusion of rest days into a well-structured training program should be considered, and an emphasis should be placed on the importance of recovery, not just for health but also for training adaptations and performance (28).…”
Section: Reducing Exercise Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…Low energy availability (LEA) occurs when either the energy intake is too low or the energy output through training is too high, leading to an insufficient amount of energy left to maintain normal physiological functions such as bone health, cardiovascular health, immune function, and menstrual function in female athletes [1][2][3][4][5][6]. Both athletes and ballet dancers are driven by strong internal and external pressure to achieve optimal performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Excessively controlling the athlete could also have an effect not only during but also after the athletic career, physiologically and psychologically [ 4 ] For example, if the coaches restrict the athletes’ food intake, it could lead to relative energy deficiency in sports (RED-S) and studies have shown that athletes who have suffered from RED-S could be at increased risk of cardiovascular diseases due to altered cholesterol metabolism [ 8 , 9 ]. Moreover, athletes with RED-S, especially during adolescence, are prone to low bone mineral density and decreased peak bone mass which is a predictor for bone fractures [ 10 , 11 , 12 ]. In addition, studies have shown that, possibly due to excessive pressure from coaches, athletes could experience depressive symptoms [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%